Desain Jaringan Komputer Terintegrasi Menggunakan Arsitektur Campus LAN: Campus LAN; Arsitektur Enterprise; Infrastruktur & Keamanan Jaringan - Jeckson Sidabutar (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2020)
The development of Information and Communication Technology (ICT) to access and provide information quickly and accurately becomes very important for an organization (commercial, tertiary, government, or individual). With the rapid development of ICT, it is necessary to consider the dangers and disadvantages of misuse in local network services or in internet-based applications. Campus LAN (Local Area Network) architecture was chosen as the standard used in computer network design. The network architecture approach in this study is a enterprise architecture approach that is used for organizational logic and planning throughout the organization and aims to determine how information technology will support business processes. This method begins by identifying the infrastructure and network security needs, as well as how the information technology system supports the process of activities for all parts of education, administration and other services.